Evaluation of Infertility-related Stress and its Associated Factors in Infertile Clients: A Cross-Sectional Study - Fatemeh Jafar zadeh-Kenarsari; Ladan Ahmad-Amraji; Kobra Abouzari-Gazafroodi (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Infertility is a painful emotional experience associated with stress. Objectives: The present study aimed at determining infertility-related stress and its associated factors in infertile clients referred to the infertility clinic of Al-Zahra hospital in Rasht, Iran, in 2019. Methods: The present cross-sectional study was performed on 200 clients undergoing infertility treatment, selected by the convenience sampling method, and completed the Copenhagen multi- centre psychological infertility-fertility problem scales (COMPI-FPSS). Descriptive and inferential statistics (the Kolmogorov-Smirnov, Mann-Whitney, Kruskal-Wallis, Chi-square, and t-tests, as well as the Spearman correlation coefficient, AVONA, and multiple linear regression) were used to analyze the data in SPSS version 16. Results: The results showed that the mean total score of infertility stress was 28.67±9.85 in the study subjects. The mean scores obtained in personal, marital, and social domains of COMPI-FPSS were 15.29±5.39, 7.43±3.72, and 5.95±2.47, respectively. A significant difference was observed in the stress score between males and females (P<0.001). There was a significant relationship between income adequacy (P=0.005), frequency of unsuccessful infertility treatment (P=0.001), duration of treatment (P=0.009), and infertility-related stress. Conclusion: Infertile subjects experienced more stress in the personal domain compared to other domains. Stress scores were significantly associated with gender, financial status, frequency of unsuccessful infertility treatment, and the duration of treatment variables. Therefore, providing counseling services and psychosocial interventions infertility treatment clinics in order to meet the psychological needs of infertile clients is an undeniable necessity.